2021
DOI: 10.1200/jco.20.01540
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Gastrectomy for Gastric Cancer (LOGICA): A Multicenter Randomized Clinical Trial

Abstract: BACKGROUND The oncological efficacy and safety of laparoscopic gastrectomy are under debate for the Western population with predominantly advanced gastric cancer undergoing multimodality treatment. METHODS In 10 experienced upper GI centers in the Netherlands, patients with resectable (cT1-4aN0-3bM0) gastric adenocarcinoma were randomly assigned to either laparoscopic or open gastrectomy. No masking was performed. The primary outcome was hospital stay. Analyses were performed by intention to treat. It was hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
124
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(157 citation statements)
references
References 31 publications
14
124
1
3
Order By: Relevance
“…In this enumeration, level 1 evidence reporting on laparoscopic total gastrectomy for advanced cancer is lacking. However, a Dutch multicenter randomized controlled trial (LOGICA trial [NCT02248519]) recently reported laparoscopic total gastrectomy for patients with predominantly advanced cancer to be safe and feasible [18]. In addition, no differences regarding postoperative morbidity, short-term oncological outcomes, and quality of life were reported, although laparoscopic gastrectomy was associated with less blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…In this enumeration, level 1 evidence reporting on laparoscopic total gastrectomy for advanced cancer is lacking. However, a Dutch multicenter randomized controlled trial (LOGICA trial [NCT02248519]) recently reported laparoscopic total gastrectomy for patients with predominantly advanced cancer to be safe and feasible [18]. In addition, no differences regarding postoperative morbidity, short-term oncological outcomes, and quality of life were reported, although laparoscopic gastrectomy was associated with less blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the CLASS-01 ( 11 ) and KLASS-02 trials ( 12 ) updated their results of long-term outcomes, indicating that locally AGC patients with LDG had similar long-term survival rates compared to open distal gastrectomy. Moreover, the LOGICA trial ( 13 ), which compared the LG with OG for treatment of AGC in the Western population, reported comparable outcomes including postoperative complications, length of hospital stay, R0 resection rate, lymph node yield, and 1-year overall survival (OS) rate. Therefore, in order to summarize the current high-quality evidence, we performed this meta-analysis of RCTs to compared the short- and long-term outcomes of LG versus OG for patients with AGC.…”
Section: Introductionmentioning
confidence: 99%
“…3 Due to the well-established differences in tumor biology and adverse prognostic factors between gastric adenocarcinoma from Eastern and Western countries, I will limit the discussion to the one Western RCT available. 4 In the Laparoscopic Versus Open Gastrectomy for Gastric Cancer (LOGICA) trial, investigators from ten experienced upper gastrointestinal centers in the Netherlands reported short-term outcomes of 227 patients. 4 In summary, laparoscopic and open gastrectomy were the same with no differences in hospital length of stay, postoperative complications, and lymph node evaluation.…”
mentioning
confidence: 99%
“…4 In the Laparoscopic Versus Open Gastrectomy for Gastric Cancer (LOGICA) trial, investigators from ten experienced upper gastrointestinal centers in the Netherlands reported short-term outcomes of 227 patients. 4 In summary, laparoscopic and open gastrectomy were the same with no differences in hospital length of stay, postoperative complications, and lymph node evaluation. Interestingly, there was also no difference in quality of life between MIS and open surgery.…”
mentioning
confidence: 99%